ASHLEY GRAHAM ON INSTAGRAM AND THE REPRESENTATION OF LARGER WOMEN - Soares, Regina (Revista Gênero e Interdisciplinaridade, 2022)
This article aims to analyze the fashion, media and Instagram interactions of women that fall outside of beauty standards, which help influence other women’s self-esteem, as well as what is considered the “perfect body” and how a model has worked to break this imposition. A case study of the American model and activist Ashley Graham displays a singular fashion trajectory throughout the years and how it broke paradigms, enabling the plus size market and motivating women around the world to share their own photos without filters and/or digital manipulation on social media.